Contribution of ‘Addak’and ‘Bindi’ in Non word Error Pattern analysis of Punjabi Typed Text - Bhagat, Meenu (International Journal of Computer Sciences and Engineering, 2025)
Error pattern analysis of a language is helpful in language related technology, such as creation of Natural Language Interfaces Spell Checker and Corrector, Machine Translation, Optical Character Recognition, Spell Checker and Corrector etc. It includes analysis of various types of errors (insertion, deletion, transposition, substitution, run-on, split word error) Positional analysis, Word length effects, Phonetic errors, First position error analysis, Keyboard effects etc. This paper mainly focuses on the contribution of ‘Addak’ and ‘Bindi’ in Statistical Error analysis of Punjabi typed text. It also compares results of insertion and deletion error results of ‘Addak’ and ‘Bindi’and its overall contribution in total number of errors. It also presents a brief overview of difficulties in automatic text error correction in Punjabi Typed Text. This paper is based on the analysis done on 20000 misspelled words generated by typists.